NATUFIAN INTERACTIONS ALONG THE JORDAN VALLEY. (December 2015) - Edwards, Phillip C.
Abstract : Building on recent observations made by Belfer-Cohen and Goring-Morris, this study proposes that a zone of intensive interaction existed between communities in the Jordan Valley during much of the Early Natufian period ( c. 12, 500–11, 000 calbc ). Recently published data demonstrate distinctive and even unique links between open-air Jordan Valley sites. Whereas some models have utilised specific types of material culture (e.g. bone artefacts or art items) to identify cultural provinces in the Natufian, this enquiry uses multiple categories of evidence (site types, shared artefact types, artefacts with close stylistic similarities, embodied behavioural practices, and raw material movements) to propose a Natufian sub-region in the Jordan Valley. The likely existence of a post-Lisan "Damya Lake" is suggested as a rationale for extensive north–south contexts south along the Rift Valley, especially for the transport of heavy materials such as basaltic rock. In the future, scientific techniques such as the isotopic analysis of human skeletal remains, elemental characterisation of raw material source, and reliable dating of excavated sites will prove to be decisive in evaluating the model.